The Influence of Product Quality, Brand Image, and Trust on Purchasing Decisions of Garnier Products in Batam - Eky Priyono; Wasiman Wasiman (Komunitas Dosen Indonesia, 2024)
Specifically, this research aims to examine the factors that influence customers' purchasing decisions in Batam regarding Garnier items, specifically focusing on trust, product quality and brand image. No exact figures are given regarding the total number of people who have purchased or utilized Garnier products. Using the Lemeshow algorithm, a sample of 100 respondents was selected using purposive sampling. Data were analysed using a multivariate linear regression model that took into account data quality assessments, classical assumptions, impacts and hypotheses. Product quality influences purchasing decisions by 17.5%, brand image by 24.4%, and trust by 70.5%, according to the findings of a multiple linear regression study. An additional 58.9 percent of purchase variance can be explained by factors including product quality, brand image, and trust., according to the coefficient of determination (R2) test results. Furthermore, t-tests and F-tests demonstrate that the purchasing decisions of Garnier products in Batam are positively and significantly influenced by product quality, brand image, and trust, both individually and collectively. Furthermore, both t-tests and F-tests were conducted to assess the individual and collective impacts of these variables. The findings show that product quality, brand image, and trust each have a positive and significant influence on the purchasing decisions of Garnier products in Batam, both independently and collectively. The significance of these characteristics in influencing customer behaviour is also visible, and trust plays a very important role. The findings of this research highlight the importance of trust, coupled with product quality and brand image, as factors influencing Batam consumers' purchasing decisions to purchase Garnier goods. For marketers and business strategists, these insights underline the need to prioritize building and maintaining consumer trust, ensuring high product quality, and fostering a strong brand image to enhance customer acquisition and retention.